Grupowanie ekonomicznych szeregów czasowych - Rozkrut, Dominik (Clustering of economic time series, 2006)
The paper discusses the clustering of time series of the same economic variables for different territorial units. Some of the variables may display the same or very similar trajectory, so it may be possible that they share common data generation process, which is a stochastic process. Some of the analyzed time series may be then considered as different outcomes of the same underlying stochastic process. Much attention has been recently devoted to the study of common features of time series (e.g. common trends), especially in econometrics. The paper presents and discusses the example of the application of the clustering methods in grouping time series in search for similar behaviors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 206-213